Potenciais efeitos da nucleação e de filtros ecológicos exercidos por árvores emergentes sobre o recrutamento de plântulas no cerrado denso - Santos, Simony Monteiro dos (2023)
Several processes can affect the structure, composition, growth, mortality and regeneration of the plant assemblage of a biological community. Among these processes, seed dispersal is one of the fundamental steps for the structuring and regeneration of vegetation, as it is from there that plant species seek new areas to establish new plants. In turn, several factors (intrinsic and extrinsic) can influence the seed dispersal process and, consequently, can affect the profile of the plant assemblage in the community. Therefore, some plant species are considered ecological or ecosystem engineers because they enable considerable changes in the local environment. Therefore, many researches have focused their studies on these species and especially large trees that stand out in the landscape. This is the case of emerging trees, which are large plants that surpass the canopy formed by the plants in their surroundings, and can have considerable ecological roles, regulating the functioning of the forest and providing significant effects on the distribution and abundance of many organisms. But understanding how large trees influence their community, within the range of facilitating or restricting the recruitment of plant species, is still limited. Therefore, the nucleation and facilitation mechanism play a fundamental role in savanna environments, since under the canopy the microclimatic and soil conditions are more favorable for seedlings than in fully open areas. However, how these effects work in closed savannas is still scarce, requiring further studies to better understand the process in dense savannah areas. Thus, the research aims to evaluate the influences of the effects of nucleation and ecological filters exerted by emerging trees on the recruitment of seedlings in the dense cerrado. The results of this study demonstrate the performance of emerging plants in dense cerrado, providing evidence that the nucleation of zoochoric seeds is not predominant, different in isolated trees, and despite this, the emergence of zoochoric seedlings is greater than in the surrounding vegetative stratum. However, even with greater emergence, the vegetation density of adult individuals is lower compared to the surrounding area. In summary, we can see that the emerging microenvironments produce complex patterns that will restrict or expand, at different and continuous moments, the plant establishment, resulting in the floristic profile under the emerging canopies. Therefore, this research presents important results that have the potential to contribute to the understanding of community dynamics, management and conservation of the cerrado.